(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this thesis the Depiction of village is at the center of Indian realm. It is being discussed in each field be it politics, literature, philosophy, or history. In Indian English fiction it is the most popularly discussed theme which is scarcely difficult to disregard or overlook. It has influenced each part of Indian English Fiction. Literature and rural narrative is still left untold at certain closures thus I might want to make an unassuming endeavour in re-inventing the rural narratives in the light of Indian English Literature. The present thesis is an endeavour to analyze the village writings of almost completely known in the realm of Indian fiction in English. The whole Indian English writings can be partitioned into two parts most definitely Pre and Post-Independence period. The foremost writings which have been fundamentally and logically discussed in this paper have a place with the post-independence period which has been a period of astonishing richness in the creation of rural literature